Mapping of Flood Prone Areas in West Lombok Based on Analytic Hierarchy Process and Geographic Information System - Nuzla Af’idatur Robbaniyyah; Syechah, Bulqis Nebulla; Naoval Husni; Marwan; Lailia Awalushaumi (Mandalika Mathematics and Educations Journal, 2024)
The development and management of flood-prone information systems is needed by many parties, especially the public. In this research, the Analytic Hierarchy Process (AHP) presents an approach to detecting flood-prone areas by combining it with a Geographic Information System (GIS). AHP analysis is used to determine the weight and value of each assessment criterion, and then the results are integrated into the GIS system to produce a flood forecast map. The results obtained show that mapping of flood-prone zones can be carried out rationally and consistently based on AHP by considering four criteria, namely land use, soil type, slope, and rainfall. The results of the analysis of the zoning map show that the areas with a high level of flood vulnerability are on the north and west sides. The area around the Lembar port has a high level of vulnerability. Eyat Mayang Village also has a high level of vulnerability. Locations with a high level of flood vulnerability, caused by flooding through rivers located not far from the sea estuary.